Spectrum of Domestic Violence against Madheshi Women in Nepal - Tiwari, Sushma (Academic Voices: A Multidisciplinary Journal, 2016)
Madheshi society. For this study 350 currently married women aged 15-49 years were selected from Parsa district by using systematic random sampling. The in Parsa district of Nepal as it is prevailing in other developing countries. Madheshi women face domestic violence from various sources. Violence against women is practiced in Nepali society on the basis of discriminatory social, cultural, economic, religious and political traditions and beliefs. The violence and inhuman treatment such as sexual assault, rape and naked parading serve as a social mechanism to maintain women’s subordinate position in society. They are targeted as a way of humiliating entire Madheshi communities in Nepal. Social exclusion of Madheshi women, poor education, unemployment, low exposure, less autonomy in decision making, weak implementation of legal system etc. largely influence women’s status. Academic Voices Vol.5 2015: 67-72